Early intervention of children with disabilities - Jachova, Zora; Dimitrova Radojichikj, Daniela; Chichevska Jovanova, Natasha (Journal of Special Education and Rehabilitation, 2004)
The aim of this paper is to give survey of previous experiences of early intervention system worldwide and in the Republic of Macedonia. The experiences show that good early intervention systems function in many countries; others, started much later in realization of this process. But there are some countries where the organization of services for early intervention is in initial stage. The Republic of Macedonia possesses modest experiences considering the way of organization of early intervention of children with disabilities. In the context, we locate the problem in lack of established mechanisms for coordination between relevant institutions, based on legislation. The condition in the Republic of Macedonia points out to the necessity to animate all considered sides in organizing the process of early intervention, which will enable creating a model based on positive worldwide experiences, modified in Macedonian context, as a prerequisite for successful social integration.
Раната интервенција на децата со пречки во развојот
Keywords: early intervention, children with developmental disabilities